Effect of linex treatment on IFN-γ and IL-4 in mice infected with Trichinella - Shimaa Attia Atta; Zeinab H. Fahmy; Eman A.H. Selim; Tarek Aboushousha; Reham Refaat Mostafa (BMC Infectious Diseases)
Abstract Trichinellosis is a zoonotic, foodborne parasitic infection causing muscle damage. This study investigated the potential therapeutic effects of the commercially available probiotic treatment Linex, both alone and in combination with Albendazole (ALB), on the intestinal and muscular stages of Trichinella spiralis infection in mice, assessing outcomes through parasitological, immunological, and histopathological measures. This study is the first to demonstrate the synergistic effect of combining the commercially available probiotic Linex with Albendazole for trichinellosis treatment. By enhancing both parasitological and immunological outcomes, this combined therapy not only significantly reduces parasite burden but also modulates the immune response, shifting it toward a protective Th1 profile. In parasitological terms, the highest adult and larval count reduction was observed in combined Linex and Albendazole treatment (100%, 97.7%) respectively. Lesser percentage of reduction were recorded in Linex alone therapy (43.2%, 88.4%) respectively. Histopathologically there was amelioration of the inflammatory cellular infiltration in all treated groups with best results in combined Linex and Albendazole treatment. Immunologically, serum IFN-γ levels increased significantly in all treated groups with highest levels in combined Linex and Albendazole treatment, while IL-4 and IL-13 level decreased significantly in all treated groups with best results observed in Linex alone treatment. To conclude; combined Linex and Albendazole treatment of mice infected with T. spirals could ameliorate the infection and improve the immune response.